Liver abscess and jundice due to fasciol hépatic: a propósito de una observación - Estapé, Gonzalo; Schneeberger, Federico; Abascal, Winston (Cirugía del Uruguay, 1977)
Diagnosis was established in a patient suffering from distomatosis hepatica due to fasciola when the parasite was found in the main biliary tract. The paper contains a review of this condition which includes its frequency, biological cycle, clinical and laboratory picture, possibilities for diagnosis, anatomopathological characteristics and treatment.